(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2025)
This article focuses on analyzing some perspectives, changes, and continuities in the content of History at the secondary level in the province of Buenos Aires, using as its object and backdrop the conceptions and representations of both nation and nationalism, and their current meanings in secondary school. To this end, the text examines a selection of textbooks intended for third-year students of the ‘New Secondary School’ in Argentina. The ‘Desert Campaign’, which took place in the last quarter of the 19th century in the south of what is now Argentina, is a privileged lens for approaching the complex framework upon which more general issues such as nation, nationalism, and the place of subaltern groups in 21st-century school education are constructed and addressed. Likewise, this text problematizes the discourses that emerge in some educational materials for compulsory school education in our country.